Association between plasma testosterone and work-related neck and shoulder disorders among female workers - Kaergaard, A.; Hansen, Åse Marie; Rasmussen, Kurt; Andersen, Johan Hviid (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'The aims were to study the association between anabolic hormone testosterone in plasma and the presence of musculoskeletal disorders among female workers and to study the association between changes in testosterone and changes in musculoskeletal complaints.' ' METHODS ': 'In a cross-sectional design 145 women from 2 different industries filled out questionnaires about current musculoskeletal complaints, participated in a clinical examination of the neck and upper extremities, and gave a blood sample for the analysis of free testosterone in plasma. Individual characteristics, psychosocial job factors, and stress reactions were evaluated by questionnaires. In a follow-up study a subgroup of 73 sewing machine operators from the cross-sectional study was reexamined after 1 year.' ' RESULTS ': 'The group of women with clinically verified neck or shoulder disorders had significantly lower plasma testosterone than the women with no disorders. Furthermore, the testosterone level showed a negative association with age and a positive association with smoking and body mass index. Changes in pain status or clinically diagnosed musculoskeletal disorders were not associated with changes in testosterone levels. However, this finding may well be due to a strong plant influence in that marked changes in testosterone levels were observed for 2 of the 3 participating plants.' ' CONCLUSIONS ': 'There is some indication of an association between musculoskeletal disorders in the neck and shoulders and a low level of free plasma testosterone. The study failed to clarify the associations found between changes in testosterone and changes in musculoskeletal complaints over time.
Keywords: anabolism; biomarker; body mass index; MSD; musculoskeletal disorder; pain; repetitive work; smoking; stress